POTENCY OF DREGS COCONUT FERMENTATION (COCOS NUCIFERA) AS AN ALTERNATIVE FEED FOR FISH AND POULTRY 'PA-BIO’ - Yolanda Fitria Syahri; S. Syahrir (Universitas Sembilanbelas November Kolaka, 2016)
People of Kolaka accustomed to using coconuts as well be used as a food supplement or a mixture of additives in processed foods, cakes and other confectionary. Therefore utilizing coconut pulp as feed fish and poultry should be made to minimize the potential for household waste. Feed from coconut pulp is a transfer of science and technology to the people who are expected to help poor people to be productive. Fermentation is one method to process coconut pulp into feed ingredients. The fermentation process is done by using spores of Aspergillus niger. The fermentation process is done in stages, by aerobic fermentation followed by anaerobic fermentation (enzymatic process). In short the process of making feed